Viscous dissipation effect on entropy generation for non-Newtonian fluids in microchannels☆ - HUNG, Y (PERGAMON-ELSEVIER SCIENCE LTD, THE BOULEVARD, 2008)
An analytical study on the viscous dissipation effect on entropy generation in fully developed forced convection for single phase non-Newtonian fluid flow in circular microchannels is reported. in the first-law analysis, closed form solutions of the temperature distributions in the radial direction for the models with and without viscous dissipation term in the energy equation are obtained. In the second-law analysis, the two models are compared by analyzing their relative deviations in dimensionless entropy generation and Bejan number for different Brinkman number and power-law index. The findings show that under certain conditions the viscous dissipation effect on entropy generation in microchannels is significant and should not be neglected. (C) 2008 Elsevier Ltd. All rights reserved.